2006
DOI: 10.11646/zootaxa.1180.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The morphology, higher-level phylogeny and classification of the Empidoidea (Diptera)

Abstract: A cladistic analysis of the Empidoidea and basal lineages of the Cyclorrhapha, based on morphological characters, confirms the monophyly of both groups as well as that of the                    Eremoneura. The resulting final trees are used to revise the classification of the Empidoidea to include the following five families: Empididae, Hybotidae, Atelestidae (including Nemedininae n. subfam.), Brachystomatidae rev. stat. (comprising the subfamilies Brachystomatinae, Ceratomerinae and Trichopezinae), and Dolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
295
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(303 citation statements)
references
References 70 publications
5
295
1
2
Order By: Relevance
“…2). The swollen basitarsus is a strong synapomorphy of the Hilarini (Sinclair and Cumming, 2006) and is found in the earliest hilarine fossils from ca. 145 million years ago (Cumming, personal communication, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2). The swollen basitarsus is a strong synapomorphy of the Hilarini (Sinclair and Cumming, 2006) and is found in the earliest hilarine fossils from ca. 145 million years ago (Cumming, personal communication, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, given that Microsania spp. are known to have smoke- The total sampling effort was 10 9 45 min N = 2 detecting glands (Sinclair and Cumming 2006) and a preference to swarm within the smoke itself (Snoddy and Tippins 1968;Klocke et al 2011), presumably for mating, although mating has rarely been observed (Chandler 1978;personal observation HN). As neither the food resources needed nor the oviposition requirements are known, it remains an open question whether Microsania spp.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, considering the high conservation value of this group of insects (many are red-listed) and that conventional methods of sampling are destructive and require a large effort, a more efficient sampling method would be beneficial, and especially one that does not kill the insects sampled. As smoke seems to contain important chemical cues that several species use to detect and navigate towards fire (Brues 1950;Evans 1966;Schütz et al 1999;Sinclair and Cumming 2006), we decided to try to sample insects by generating smoke. The method would, of course, only work for smokeattracted insect species hence ignoring species that navigate by other means or arrive at a burnt site with a considerable time delay.…”
Section: Introductionmentioning
confidence: 99%
“…In the system outlined by Saigusa (2006), the dipteran A 1 (as used in McAlpine 1981) is homologized with the mecopteran CuP, and consequently CuA 1 (of McAlpine) is termed M 4 , CuA 2 is CuA, the anal cell is cell cua and the anal vein (A 1 +CuA 2 ) is CuP+CuA. Homologies of the male terminalia follow those of Sinclair & Cumming (2006). The term 'bristle' is used for differentiated large setae on the head, mesonotum and legs bearing a particular name or one of a series with a particular name, e.g., notopleural bristle, dorsocentral bristle, anterodorsal bristle.…”
Section: Methodsmentioning
confidence: 99%
“…Adipsomyia is herein removed from the subfamily Clinocerinae and assigned to the subfamily Trichopezinae of the Brachystomatidae (see Sinclair & Cumming 2006). This transfer is supported by the modified female terminalia (upright and stout cercus, female sternum 8 closely associated to anteroventral corner of tergum 8), although tergum 8 lacks an internal apodeme.…”
Section: Geographical Distributionmentioning
confidence: 99%